ACCURACY OF QUR'AN INTERPRETATION: Semiotic Approach - Iskandar Zulkarnain; Ade Naelul Huda; Abdullah Safei (Indonesian Journal of Islamic Studies (IJIS), 2026)
This study aims to evaluate the accuracy of the interpretation of the Qur'an text through a semiotic approach, which can provide a holistic understanding of the mechanism of interpretation and the validity of the interpretation method used by the mufasir. This study examines three main works of interpretation and applies qualitative content analysis to uncover the semiotic aspects underlying the interpretation of sacred texts. This research also seeks to answer research questions regarding the validity of the interpretation methodology in representing the meaning of the Qur'an text as a whole. The results of the study show that there are certain patterns in the use of symbols and signs that significantly affect interpretation, thus demanding an in-depth understanding of the semiotic framework in the study of interpretation. The contribution of this research is expected to enrich the study of interpretation and provide strategic recommendations for further research in the field of Qur'an studies.